2022
DOI: 10.1007/s00590-022-03269-0
|View full text |Cite
|
Sign up to set email alerts
|

Changes in coronal alignment of the hip joint after medial opening wedge high tibial osteotomy

Abstract: Purpose An observation was made by the senior author of this paper that patients reported changes in their hip function after a medial opening wedge high tibial osteotomy (MOHTO) for varus pattern osteoarthritis. Alignment changes at the hip after MOHTO have not been previously documented. This study assesses coronal alignment changes at the hip after MOHTO. Methods We retrospectively analysed pre- and post-operative lower limb alignment radiographs of pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
1
0
0
Order By: Relevance
“…Thus, theoretically, HTO of the genu varum increases the hip joint reaction force and energy consumption by the hip abductor, which could also aggravate femoral adduction due to weakness of the hip abductor over time. 1,12,26 In our study, we found a greater increase in hip adduction with time after HTO, which could be evidence of the aforementioned theoretical assumption in hip joint change (femoral adduction) and show, to the best of our knowledge, its aggravation from immediately postoperatively to 2 years after HTO. This increasing trend in femoral adduction after HTO could also be a possible cause of the consistent increase in KJLO after HTO.…”
Section: Discussionsupporting
confidence: 82%
“…Thus, theoretically, HTO of the genu varum increases the hip joint reaction force and energy consumption by the hip abductor, which could also aggravate femoral adduction due to weakness of the hip abductor over time. 1,12,26 In our study, we found a greater increase in hip adduction with time after HTO, which could be evidence of the aforementioned theoretical assumption in hip joint change (femoral adduction) and show, to the best of our knowledge, its aggravation from immediately postoperatively to 2 years after HTO. This increasing trend in femoral adduction after HTO could also be a possible cause of the consistent increase in KJLO after HTO.…”
Section: Discussionsupporting
confidence: 82%